Buddhist Encounter with Other World Religions - J. G. Arapura (Journal of Dharma, 1995)
The theme of encounter of world religions is continued in this issue of the Journal of Dharma. This time it has to do with Buddhism's encounter with other world religions. As such it has three distinct constituent parts to be considered, which are world religions, Buddhism and encounter, but all the three in the unified context of what this issue deals with.